Etika Eudaimonisme dalam Buddhisme - Umah, Siti Rokhmatul (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2021)
One of the Eastern Philosophy teachings that emphasizes the moral practices and ethical teachings is Buddhism. However, these teachings are still scattered and not yet systemised. So, it is necessary to identify the pattern and form of the ethics. At first glance, ethics in Buddhism has the same pattern as the ethics of eudaimonism that is made by Aristotle which contains several aspects, namely teleological aspects, self-development, and virtue. This studies employs Aristotle’s ethical theory as a theoretical framework to dialogue, analyze, and build ethical concepts that is occurred in the teachings of Buddhism. There are three characters in Aristotle’s ethical philosophy, namely teleology, self-development, and virtue. The data were gathered through library research and analysed by interpretation and description methods. The approach that is employed in this paper is a philosophical approach that seeks to find the basic philosophical structure of the teachings of Buddhism in the concept of Aristotle’s ethics of eudaimonism. This study shows that the ethics of Buddhism contain teleological aspects that in line with the ethics of eudaimonism, namely, self-development aspects, and virtue aspects. According to Buddhism, the goal of all human action is to attain the highest happiness, namely Nibbana (detachment from suffering). To achieve it one must practicing the Noble Eightfold Path. [Salah satu ajaran filsafat Timur yang menekankan praktik-praktik moral serta ajaran etika adalah Buddhisme. Namun, ajaran-ajaran etika tersebut masih berserakan dan belum tersistem. Maka, perlu diidentifikasi corak atau bentuk etikanya. Sekilas, etika dalam Buddhisme memiliki corak yang sama dengan etika eudaimonisme dari Aristoteles yang mengandung beberapa aspek, di antaranya, aspek teleologis, pengembangan diri, dan keutamaan. Dalam tulisan ini, penulis menggunakan teori etika Aristoteles sebagai kerangka teoritis dalam mendialogkan, menganalisis, dan membangun konsep etika yang terdapat dalam ajaran Buddhisme. Dalam filsafat etika Aristoteles, terdapat tiga karakter, yaitu teleologi, pengembangan diri, dan keutamaan. Data-data dikumpulkan melalui studi kepustakaan/library research dengan menggunakan metode analisa yaitu interpretasi dan deskripsi. Pendekatan yang digunakan dalam tulisan ini adalah pendekatan filosofis yang berupaya menemukan struktur dasar filosofis dari ajaran Buddhisme dalam konsep etika eudaimonisme Aristoteles. Artikel ini menemukan bahwa etika dalam Buddhisme mengandung aspek yang terdapat dalam etika eudaimonisme, yakni aspek teleologi, yakni pengembangan diri, dan aspek keutamaan. Menurut Buddhisme, tujuan dari segala tindakan manusia adalah untuk mencapai kebahagiaan tertinggi, yaitu Nibbana (terlepasnya dari penderitaan). Untuk mencapainya adalah dengan mempraktikkan Jalan Mulia Beruas Delapan.]